Outcome of Secondary Interval Rheolytic Thrombectomy after Localized Intra-Arterial Catheter-Directed Thrombolysis through Power-Pulse Spray Technique in Cases of Partially Successful or Failed Primary Rheolytic Thrombectomy - Biswajit Sahoo; Satyapriya Mohanty; Siddhartha Sathia; Rudra Pratap Mahapatra; Manoj Kumar Nayak; Ritesh Panda; Manas Kumar Panigrahi; Sourav Kumar Mishra; Prakash Kumar Sasmal; Pankaj Kumar; S. Manawar Ali; Nerbadyswari Deep Bag; et al. (The Arab Journal of Interventional Radiology)
Objectives The aim of this study was to evaluate the safety and effectiveness of secondary interval AngioJet rheolytic thrombectomy after localized intra-arterial catheter-directed thrombolysis (CDT) through power-pulse spray (PPS) technique in partially successful or failed primary AngioJet rheolytic thrombectomy cases of acute and subacute peripheral artery thrombosis.